A Note on the Balto-Slavic and Indo-European Background of the Proto-Slavic Adjective *svętъ ‘Holy’ - Majer, Marek (Studia Ceranea, 2017)
The standard etymological explanation of the Proto-Slavic adjective *svętъ ‘holy, saint’ – a word of extreme literary, cultural and religious importance in the Slavic world – concentrates on the formal match with Lithuanian šventas ‘id.’ and Avestan spəṇta‑ ‘life-giving, holy’ (PIE *ḱwen‑to‑, from the root *ḱwen‑). This article highlights the verbal formation seen in Latvian svinêtsvin svinẽjo ‘celebrate, venerate’, generally recognized as another reflex of the root *ḱwen‑ in Balto-Slavic, but without due attention to the formal implications. It is argued that both in Av. and in BSl. the adjective spəṇta‑/*svętъ behaves as an item participating in the so-called ‘Caland System’ (a set of arbitrary morphological alternations reconstructible for Proto-Indo-European).